1997
DOI: 10.1002/(sici)1097-4652(199707)172:1<1::aid-jcp1>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Growth stimulation of colorectal carcinoma cells via the c-kit receptor is inhibited by TGF-β1

Abstract: Activation of the receptor tyrosine kinase c-kit by the kit-ligand, also known as stem cell factor (SCF), is essential to melanocyte and germ cell development and during the early stages of hematopoiesis. Deregulated expression of c-kit has been reported in malignancies affecting these lineages, i.e., myeloid leukemias, melanomas, and germ cell tumors. In addition, c-kit and SCF are coexpressed in some breast and colorectal cancer (CRC) cells, raising the question of whether c-kit serves an autocrine role in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…More recently, Sammarco et al detected KIT-positive staining in the epithelium of the neoplastic colon in 25% of patients examined (10). In a previous preliminary analysis conducted on a small number of patients, we reported KIT immunoreactivity in several malignant mucosa specimens compared to normal counterparts (38). The present evaluation of KIT expression using a polyclonal antibody recommended for accurate GIST diagnosis (39) and using a larger number of CRC cases at different disease stages as well as adenomas, confirms that KIT overexpression is rare in these tumor forms.…”
Section: Discussionmentioning
confidence: 47%
“…More recently, Sammarco et al detected KIT-positive staining in the epithelium of the neoplastic colon in 25% of patients examined (10). In a previous preliminary analysis conducted on a small number of patients, we reported KIT immunoreactivity in several malignant mucosa specimens compared to normal counterparts (38). The present evaluation of KIT expression using a polyclonal antibody recommended for accurate GIST diagnosis (39) and using a larger number of CRC cases at different disease stages as well as adenomas, confirms that KIT overexpression is rare in these tumor forms.…”
Section: Discussionmentioning
confidence: 47%
“…Similarly, reports offering a contrasting view on the role of c-KIT in CRC have been published: Bellone et al showed that increased immunoreactivity to c-KIT is associated with neoplastic colonic tissues [10], whereas other groups have suggested that immunohistochemical staining for c-KIT is a rare event in human CRC [11,12,13]. A possible reason for these conflicting results is that the authors did not correlate the expression of c-KIT in both the normal and neoplastic colon tissue for each patient examined.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to CRC, while some authors have demonstrated the expression of both c-KIT transcript and protein [10], a number of other reports have shown rare if any expression of c-KIT in CRC tissue [11,12,13]. Most of these studies were retrospective and not specifically aimed at investigating c-KIT expression in CRC [11,12], and did not analyze both the RNA and protein levels of c-KIT in each patient.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous expression of c-kit and SCF has been reported in colon, gastric, and lung cancer cell lines, in which a growth/migrationstimulating autocrine loop has been demonstrated (Bellone et al, 1997;DiPaola et al, 1997;Hassan et al, 1998). On the other hand, in melanomas and in breast and thyroid carcinomas a loss of expression of these molecules, in comparison with normal melanocytes and mammary or thyroid epithelium, has been described (Moretti et al, 1999;Natali et al, 1992Natali et al, , 1995Welker et al, 2000).…”
Section: Esposito Et Almentioning
confidence: 99%